Improving the legitimacy of EU economic governance: why and how? - Renaud Thillaye (WWWforEurope, 2014)
The sustainability of European economic and monetary union (EMU) has been questioned over the last few years. Criticism has focused on the missing democratic dimension behind recent governance reforms, and the lack of compensating output legitimacy. The paper considers the seriousness of this legitimacy problem. It starts by revisiting the classic division between 'input' and 'output' legitimacy in the context of EMU and finds that, given a lack of will to commit to deeper integration, governance needs to accommodate the diversity of expectations and situations of euro countries. The paper then assesses the way governance works in practice by analysing the interaction between the EU and national democracies on three similar cases: the 2011 labour market reform in Italy, the 2013 pension reform in France, and the 2014 minimum wage decision in Germany. Each of these cases is reflective of a reform related (directly or not) to a recommendation by the EU and conducted under its supervision. The analysis tends to confirm the existence of patterns of legitimation specific to EU economic governance. It suggests that the 'legitimacy problem' is manageable as long as national governments and parliaments are resolute in dealing collectively with their differences. This implies that deepening the `transnational' attributes of economic governance could be envisaged as a serious alternative to the remote prospect of a federal Eurozone.
Keywords: E02; 330; EU integration; European governance; European Monetary Union; Good governance; Institutional reforms; Welfare reform